Phase II randomised, double-blind, placebo-controlled trial to assess the efficacy and safety of MLC1501 in patients with stroke: the MLC1501 study Assessing Efficacy in post-STrOke Subjects with mOtor deficits (MAESTOSO) study protocol - Narayanaswamy Venketasubramanian; Deidre Anne De Silva; Christopher P L H Chen; Cyrus G Escabillas; John Harold Hiyadan; Johnny K Lokin; Romulo U Esagunde; Joel M Advincula; Christian Oliver C Co; Maria Epifania V Collantes; Annabelle Y Lao; Yeow-Hoay Koh; et al. (Stroke and Vascular Neurology)
Background MLC1501, consisting of four herbs, that is, Radix Astragali, Radix Angelicae sinensis, Rhizoma Chuanxiong, Radix Polygalae, has the same pharmacological properties as its precursors MLC601 and MLC901 which contain extracts of nine herbs and showed neuroprotective, anti-inflammatory and neurorestorative properties in non-clinical models, as well as clinical benefits in improving functional and neurological recovery after brain injuries.Aims To determine the efficacy of MLC1501 on motor recovery as measured by Fugl-Meyer motor Assessment (FMA) total score at 24 weeks in patients with ischaemic stroke (IS).Design A total of 300 patients aged >18 years, diagnosed with IS in the prior 2–10 days, with National Institute of Health Stroke Scale (NIHSS) total score of 8–18 and a combined score of ≥3 on NIHSS motor items 5A, 5B, 6A and/or 6B, will be randomised in a 1:1:1 ratio to receive oral placebo, MLC1501 low dose or MLC1501 high dose for 6 months. The study is governed by a Steering Committee. An independent Data Monitoring Committee oversees patient safety.Outcomes The primary outcome is mean change from baseline in FMA total score at 24 weeks. Efficacy outcomes evaluated in person at baseline, 12 weeks and 24 weeks include the FMA (total, upper extremity and lower extremity motor scores), modified Rankin Scale (mRS), Patient-Reported Outcomes Measurement Information System–Global Health (PROMIS-10) and NIHSS. Additionally, telephone assessment at week 4 includes the simplified mRS and PROMIS-10.Safety will be evaluated by standard assessments and occurrence of adverse events over the duration of the study.Discussion Interventions that enhance recovery beyond the acute period of stroke are needed. MLC1501 has a good safety profile as well as potential to be a treatment for recovery after brain injury. The results of this study will provide objective level B evidence on the efficacy of MLC1501 on long-term recovery and safety of 24 weeks of treatment among patients with IS.Trial registration number NCT05289947.